Soil characteristics under different crops in mountain environments in Pamplona, Norte de Santander - González-Pedraza, Ana; Sandoval, Steve; Escalante, Juan (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Agricultural intensification in mountain regions can alter soil quality and compromise its ecosystem functionality. Accordingly, this study evaluated the influence of land use on the physical, chemical, and biological properties of soils in agricultural and forest systems located in the Monteadentro district, municipality of Pamplona, Norte de Santander. During the 2019 rainy season, five land-use types were analyzed: strawberry, pea, tree tomato, pasture, and natural forest. In 1,000 m² plots, composite soil samples were collected at 0–10 cm depth to determine texture, volumetric water content (VWC), bulk density (BD), pH, electrical conductivity (EC), total organic carbon (TOC), and soil basal respiration (SBR). Both univariate and multivariate statistical analyses were applied (ANOVA, Kruskal–Wallis, correlations, and PCA). The results showed that land use significantly affected soil properties. Forest soils exhibited more favorable conservation conditions, with higher TOC content (2.8 %) and lower BD (0.7 g·cm-3), in contrast to agricultural soils, which presented higher BD, lower VWC and TOC, and higher SBR, likely associated with more labile organic substrates and organic matter degradation. Principal Component Analysis identified two main gradients: a physical–textural gradient (clay, VWC, EC, sand) and a biochemical–structural gradient (silt, pH, TOC, SBR), which differentiated land-use systems according to their degree of disturbance. These findings emphasize the need to implement conservation-oriented management strategies and regular soil monitoring in order to preserve soil functionality in mountain ecosystems.